The courage to teach with compassion: Enriching classroom designs and practices to foster responsiveness to suffering. Issue 1 (February 2022) - Worline, Monica C; Dutton, Jane E
Recognizing the prevalence of suffering among management teachers and students, we raise the importance of compassion as central to the practice of management teaching. To aid in understanding how suffering and compassion arise in management teaching, we call upon a theoretical view of their rhizomatic structure, which conveys the widespread, complex, and largely unspoken spreading of suffering and corresponding need for compassion in the work of management teaching. To meet this suffering with compassion, we propose two clusters of practices central to teaching that lend themselves to helping management teachers see possibilities for more skillfully intertwining suffering and compassion. The first focuses on how management teachers can design the context for teaching in ways that make compassion more likely, focusing specifically on roles and networks. The second draws upon Honneth's recognitional infrastructure to focus on how teachers can approach the relational practice of teaching with emphasis on enriching human recognition of suffering. We conclude with a caution about overly simplistic approaches and overly individualized views of compassion in the work of management teaching. We call for systemic approaches to action that will enrich our imaginations as we approach management teaching and its role in our collective responsiveness to suffering.